2013
DOI: 10.1007/128_2013_424
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Metamorphosis

Abstract: When compared to other conserved housekeeping protein families, such as ribosomal proteins, during the evolution of higher eukaryotes, aminoacyl-tRNA synthetases (aaRSs) show an apparent high propensity to add new sequences, and especially, new domains. The stepwise emergence of those new domains is consistent with their involvement in a broad range of biological functions beyond protein synthesis, and correlates with the increasing biological complexity of higher organisms. The new domains have been extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 135 publications
(172 reference statements)
0
50
0
Order By: Relevance
“…In addition to serving this canonical function, higher eukaryotic ARSs have been implicated in a variety of noncanonical functions, including inflammation (38), angiogenesis (39), translation regulation (40), gene-specific translational silencing (41), apoptosis and angiogenesis (40 -45). Specifically, recent studies reported that ARSs are implicated in tumorigenesis through the interactions between different regulators and new domains of the ARSs (46). NARS, a class II ARS, was identified as an up-regulated protein in early-stage tumor tissues in this study.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to serving this canonical function, higher eukaryotic ARSs have been implicated in a variety of noncanonical functions, including inflammation (38), angiogenesis (39), translation regulation (40), gene-specific translational silencing (41), apoptosis and angiogenesis (40 -45). Specifically, recent studies reported that ARSs are implicated in tumorigenesis through the interactions between different regulators and new domains of the ARSs (46). NARS, a class II ARS, was identified as an up-regulated protein in early-stage tumor tissues in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Leucine zipper (LZ) are also involved for the formation of complexes in higher eukaryotes but have not yet been found in aaRSs from lower eukaryotes and are therefore not described in this section. UNE‐X domains, unique domains specific to each aaRS, are not described in this section because they are not always protein‐ or RNA‐binding domains [72].…”
Section: Main Textmentioning
confidence: 99%
“…1A). These GST domains display strong homology to the GST domain of elongation factor eEF1B␥, which belongs to the theta class (4,5). Sequence alignment of the domains reveals that the GST-C subdomains are similar in size and well conserved in sequence, especially the residues involved in stabilizing the helical bundle structure, whereas GST-N subdomains are less conserved in size and sequence (Fig.…”
Section: Specific Heterodimeric Interactions Between Gst Domains-mentioning
confidence: 99%
“…Among ARSs, GST homologs are found in methionyl-tRNA synthetase (MRS) from yeast to human and are involved in MRS catalysis (6). Mammalian valyl-tRNA synthetase, glutaminylprolyl-tRNA synthetase (EPRS), the largest isoform of human cysteinly tRNA synthetase, and glutamyl-tRNA synthetase (ERS) in some species, also contain a GST domain located in their N-terminal regions (5,7). Although the functional impli-cations of these embedded GST domains vary, they appear to play roles in protein assembly and folding.…”
Section: Prevalence Of the Gst-like Domains This Tetramer Can Also Pmentioning
confidence: 99%
See 1 more Smart Citation